Preservice Science Teachers’ TPACK Development in a Technology-Enhanced Science Teaching Method Course - Tezcan Kartal; Irem Dilek (Journal of Education in Science, Environment and Health)
This study investigated preservice elementary science teachers’ TPACK development throughout a science teaching method course. The pretest-posttest control group was used in the study. At the end of the study, a self-reported TPACK measure was administered to the experimental (n=26) and control (n=23) groups. The experimental group learned about instructional technologies that can be used in science teaching; prepared technology-based science activities, shared these activities with their peers; planned and taught a mini technology-based lesson, evaluated the lesson, and replanned and retaught the lessons. The results showed that the experimental group had positive gains about how to integrate technologies into science teaching. Participants in the experimental group comprehended that teaching science with technology requires more than technical knowledge and skills and that it is essential to realize the interactions between science, technology, and pedagogy. Besides, the experimental group’s TPACK significantly differed from the control group. The implications and suggestions were given based on the results.